Stress-induced reinstatement of cocaine seeking is mediated by the kappa opioid system - Redila, Van A.; Chavkin, Charles (Psychopharmacologia, 2008)
Introduction Prior activation of the kappa opioid system by repeated stress or agonist administration has been previously shown to potentiate the rewarding properties of subsequently administered cocaine. In the present study, intermittent and uncontrollable footshock, a single session of forced swim, or acute administration of the kappa agonist U50,488 (5 mg/kg) were found to reinstate place preference in mice previously conditioned with cocaine (15 mg/kg) and subsequently extinguished by repeated training sessions without drug. Results and discussion Stress-induced reinstatement did not occur for mice pretreated with the kappa opioid receptor antagonist norbinaltorphimine (10 mg/kg) and did not occur in mice lacking either kappa opioid receptors (KOR −/−) or prodynorphin (Dyn −/−). In contrast, the initial cocaine conditioning and extinction rates were not significantly affected by disruption of the kappa opioid system. Cocaine-injection also reinstated conditioned place preference in extinguished mice; however, cocaine-primed reinstatement was not blocked by kappa opioid system disruption. Conclusion The results suggest that stress-induced drug craving in mice may require activation of the dynorphin/kappa opioid system.